An Evidence-Supported Medical Laboratory Science Program Admissions Selection Process. - CONWAY-KLAASSEN, JANICE M. (Clinical Laboratory Science)
After a recent enrollment expansion, a Medical Laboratory Science program experienced a higher than desired student attrition rate due to a number of academic and non-academic student readiness factors. In an attempt to address retention and other issues, the program completed a curriculum update and revision as well as a conversion to a hybrid or flipped classroom delivery model, but in spite of an overall improvement in student learning outcomes, the program still experienced a high level of student attrition. Program faculty then developed and implemented a two stage holistic admissions selection process, which included an interview and skills test, in an attempt to assess candidate background knowledge and abilities in an equitable manner. Comparison of student factors associated with on-time successful graduation, probation (delayed graduation), or dismissal from the program indicated that the science and prerequisite science grade point averages were significantly higher for students who graduated on-time compared to delayed or nonsuccessful (dismissed) students. Review of applicants' performance in the interview and skills test showed significant differences for multiple factors for students who graduated on-time from the program compared to delayed (probation) and non-successful (dismissed) students. Continuing reviews of program retention rates are needed, however the attrition rate for the next cohort dropped from 24% to 4% when the program focused the selection process on factors shown to be associated with successful graduation.